طبی عمل اور صحت کے شعبے میں اسلامی اخلاقیات کا تحقیقی مطالعہ: A Research Study of Islamic Ethics in Medical Practices and Healthcare Policies - Dr. Muhammad Qasim, (Al-Amīr Research Journal for Islamic Studies, 2024)
Islam considers illness as a test from Allah. Therefore, the Doctor has a sympathetic attitude towards the patient. The concept of Islam is that a person's body is the trust of Allah Almighty and its protection is the shari'ah duty of every human being. That's why the Prophet ﷺ encouraged treatment. Therefore, medicine has a close relationship with Islamic ethics. By which the sorrows, pains, sufferings, sufferings and problems of thousands of people are solved with good morals. It creates harmony in medicine, religion and social life. This knowledge of applied ethics discusses the ethical values ​​that are imposed by religion and society on the fields of medicine and wisdom. Ethics the most important role in medicine is the people belonging to this profession. These include the study of interpersonal ethics, then physician-patient ethics, and the Oath these individuals take before obtaining their professional license. In almost all the societies of the world, medicine is seen as a high and respectable profession and therefore the ethics of the people belonging to this field are also expected to be high. The field of medicine is not limited to the mere external condition of the patient, but it goes to the soul of the human body during the treatment and research and is thus connected with the evidence and signs of the creator of life and his knowledge. Besides, science and ethics of life is a broad field that includes all aspects related to life. On the contrary, generally, ethical medicine limits its scope to applied medicine. Keywords: Islamic Ethics, Medical Practices, Healthcare Policies.